2019
DOI: 10.3847/1538-4357/ab20cd
|View full text |Cite
|
Sign up to set email alerts
|

A Broadband Look at the Old and New ULXs of NGC 6946

Abstract: Two recent observations of the nearby galaxy NGC 6946 with NuSTAR, one simultaneous with an XMM-Newton observation, provide an opportunity to examine its population of bright accreting sources from a broadband perspective. We study the three known ultraluminous X-ray sources (ULXs) in the galaxy, and find that ULX-1 and ULX-2 have very steep power-law spectra with Γ = 3.6 +0.4 −0.3 in both cases. Their properties are consistent with being super-Eddington accreting sources with the majority of their hard emissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 94 publications
1
36
0
Order By: Relevance
“…Both the CUTOFF and DISKPBB models gave equally acceptable fit to the spectra of the sources (i.e., reduced chisquared, χ r 2 ∼1). For the CUTOFF model, we found that the measured photon index values for source 5 and 14 are consistent with the typical value obtained for ULXs; i.e., Γ = 2 (e.g., Annuar et al 2015 andEarnshaw et al 2019a). The measured values for source 3, 16, 22 and 23 are <2, indicating hard spectra or relatively significant absorption.…”
Section: Spectral Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Both the CUTOFF and DISKPBB models gave equally acceptable fit to the spectra of the sources (i.e., reduced chisquared, χ r 2 ∼1). For the CUTOFF model, we found that the measured photon index values for source 5 and 14 are consistent with the typical value obtained for ULXs; i.e., Γ = 2 (e.g., Annuar et al 2015 andEarnshaw et al 2019a). The measured values for source 3, 16, 22 and 23 are <2, indicating hard spectra or relatively significant absorption.…”
Section: Spectral Analysissupporting
confidence: 83%
“…However, the upper limit values are consistent with that obtained from the CUTOFF model. Annuar et al 2015 andEarnshaw et al 2019a). We obtained upper limit values for the disk temperature profile for all sources; i.e., p < 0.9, except for source 23 which we managed to get a measured value of p = 0.2 0.3 0.8 + − .…”
Section: Spectral Analysismentioning
confidence: 99%
“…This is a key consideration here, since the latter are now being detected in increasing numbers as our X-ray archives continue to grow (e.g. Middleton et al 2012Middleton et al , 2013Soria et al 2012;Pintore et al 2018Pintore et al , 2020Earnshaw et al 2019aEarnshaw et al , 2020van Haaften et al 2019;Brightman et al 2020b;Walton et al 2021), and may be of particular interest in the context of identifying good ULX pulsar candidates (e.g. Tsygankov et al 2016;Earnshaw, Roberts & Sathyaprakash 2018;Song et al 2020).…”
Section: Step 2 -Luminosity Cutmentioning
confidence: 99%
“…This is the latest member of the growing population of transient ULXs (e.g. Soria et al 2012;Middleton et al 2012Middleton et al , 2013Pintore et al 2018Pintore et al , 2020Earnshaw et al 2019aEarnshaw et al , 2020Brightman et al 2020). Remarkably, ULX3 is the third such source in the galaxy NGC 7090 alone (e.g.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 98%
“…Furthermore, as the archive of X-ray data continues to grow, and along with it the number of nearby galaxies with multiple observing epochs, an increasing number of new/transient ULXs are being reported (e.g. Soria et al 2012;Middleton et al 2012Middleton et al , 2013Pintore et al 2018Pintore et al , 2020Earnshaw et al 2019aEarnshaw et al , 2020van Haaften et al 2019;Brightman et al 2020). The high-amplitude long-term variability Although this is distinct behaviour from the known ULX pulsars, which spend extended periods at highly super-Eddington luminosities, these may be interesting objects in terms of connecting ULX pulsars to the sub-Eddington X-ray pulsar population.…”
mentioning
confidence: 99%